2015
DOI: 10.1371/journal.pone.0122393
|View full text |Cite
|
Sign up to set email alerts
|

A Promoter Polymorphism (rs17222919, −1316T/G) of ALOX5AP Gene Is Associated with Decreased Risk of Ischemic Stroke in Two Independent Chinese Populations

Abstract: No coding sequence variants of the gene encoding 5-lipoxygenase-activating protein (ALOX5AP) leading to amino acid substitutions have been identified. Therefore, variants in the ALOX5AP promoter region have received attention recently. The purpose of this study was to explore whether the promoter polymorphism rs17222919 is involved in the etiology of ischemic stroke (IS) in the Chinese Han population. We investigated the rs17222919 polymorphism by TaqMan genotyping in two independent Chinese Han samples: the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
(20 reference statements)
0
11
1
Order By: Relevance
“…Four Asian studies in three publications investigated the role of the ALOX5AP rs17222919 polymorphism 24,27,33. Random-effects meta-analysis indicated no association of the SNP with IS (OR=0.89 for G allele vs T allele; 95% CI: 0.75–1.06; P =0.175) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Four Asian studies in three publications investigated the role of the ALOX5AP rs17222919 polymorphism 24,27,33. Random-effects meta-analysis indicated no association of the SNP with IS (OR=0.89 for G allele vs T allele; 95% CI: 0.75–1.06; P =0.175) (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Then in the remaining 27 documents, 22 were excluded, including 7 reviews, 6 cases reports, 4 studies with repeated crowd, and 5 studies with unacquirable data. Finally, 5 documents [ 22 – 26 ] were included in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As reported in the original study, ALOX5AP mRNA levels were not compared between cases and controls, [ 22 , 25 ] which might also be a limitation of this study. Other limitations are listed as follows.…”
Section: Discussionmentioning
confidence: 98%
“…Our previous i n vitro promoter assay revealed that the G allele had a lower transcriptional activity than the T allele, suggesting that the −1316T/G variation reduces ALOX5AP promoter activity and consequently down-regulates gene expression. The decreased ALOX5AP transcription results in increased inactivation of the 5-LO pathway and reduces leukotriene biosynthesis, which in turn protects from IS 18 . The rs9579646 polymorphism showed no significant differences between groups and was not associated with IS in our second Chinese cohort.…”
Section: Discussionmentioning
confidence: 99%